Experimental phase diagram study of the TiAl-rich part of the Ti–Al–Ni ternary system. (March 2023) - Nakashima, Hirotoyo; Yu, Jianhui; Takeyama, Masao
Abstract: Phase equilibria of the TiAl-rich part of the Ti–Al–Ni ternary system have been studied experimentally by scanning electron microscopy and electron probe micro-analysis of heat-treated alloys. Partial isothermal sections involving the liquid, β-Ti, α-Ti, α2 -Ti3 Al, γ-TiAl and τ3 -Al3 NiTi2 phases were constructed between 1623 and 1273 K. Eight three-phase regions of the L + β + α, L + α + γ, L + β + γ, β + α + γ, L + β + τ3, β + γ + τ3, β + α2  + τ3 and α2  + γ + τ3 were derived. Extrapolations of these tie-triangles indicate the occurrence of three transition-type reactions; L + α = β + γ at around 1593 K, L + γ = β + τ3 at around 1553 K, and β + γ = α + τ3 at around 1393 K. The Ni solid solubility in the α and α2 phase is extremely low, less than 1 at.% in all studied temperature ranges. Highlights: Partial isothermal sections of the TiAl-rich part were experimentally determined at 1623, 1598, 1573, 1473, 1373, and 1273 K. Three invariant reactions were deduced from the temperature change in the phase relations. The α and α2 phases exhibit considerably small Ni solubility, less than 1 at.% in the studied temperature range.